How amytal changed psychopharmacy: off-label uses of sodium amytal (1920–40). Issue 3 (September 2019) - Gershon, Ariel; Shorter, Edward
In the early 1930s, American neurologist and psychiatrist William Bleckwenn used sodium amytal to render catatonic patients responsive, so that he could engage in talk therapy. Bleckwenn found a new, 'off-label' use for this anaesthetic and anxiolytic medication in psychiatry and, in doing so, allowed for important discoveries in the diagnosis and treatment of catatonia. Pharmacological textbooks reveal a 'label', while the Index-Catalogue of the Library of the Surgeon-General's Office reveals explorations 'off label' of barbiturates. The 'off-label' use of barbiturates facilitated talk therapy, heralding an important shift in psychopharmacy. Drugs previously only used as chemical restraints became a form of treatment for specific psychiatric diseases. The current strictures against off-label prescribing are overprescriptive and close off innovative new uses.